Optimalisasi Biaya Program Terintegrasi Melalui Akuntansi Manajemen: Studi Kasus Pada Smart Islamic Cultural Community Di Kampung Melayu Modern - Eliana; Setiawan; Muhammad Lukman Baihaqi Alfakihuddin; Rudy Fachruddin; Indra Kesuma (Bansigom Na Publisher, 2026)
Kampung Bharu is a Malay-Islamic enclave in the heart of a metropolitan area undergoing significant transformation, where traditional values interact with the demands of modernity. An integrated programme encompassing social, religious, cultural and economic activities requires efficient cost management to ensure its sustainability. The method employed was a literature review, examining academic sources relating to management accounting, Activity-Based Costing (ABC), and the cost management of integrated programmes. The research findings indicate that the application of ABC is capable of accurately identifying cost drivers and allocating resources more efficiently across each component of the community programme. The integration of ABC with Lean Accounting and Time-Driven Activity-Based Costing has proven effective in identifying idle capacity, reducing waste, and improving the operational efficiency of the programmes. This research contributes to the development of an adaptive cost management model for culture- and religion-based communities in urban areas that run integrated programmes